USING SOCIAL MEDIA PLATFORMS (TIKTOK, YOUTUBE, INSTAGRAM) TO IMPROVE ENGLISH SPEAKING SKILLS - Odilova Fotimakhon, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract  This  article  explores  the  pedagogical  potential  of  social  media  platforms, specifically TikTok, Instagram, and YouTube, in developing English speaking skills. Unlike traditional methods, social media provides learners with exposure to "authentic language"  and  "shadowing"  opportunities.  The  study  analyzes  how  micro-learning through short-form videos contributes to fluency and phonetic accuracy. It evaluates the shift from formal classroom settings to autonomous digital learning environments and discusses the reduction of Foreign Language Speaking Anxiety (FLSA) through consistent digital interaction.